A purified selenophosphate-dependent enzyme from Salmonella typhimurium catalyzes the replacement of sulfur in 2-thiouridine residues in tRNAs with selenium. - Veres, Z (1994)
A tRNA-modifying enzyme tentatively termed tRNA 2-selenouridine synthase was purified by a five-step procedure that resulted in 50-60% pure preparations. This enzyme catalyzes the conversion of a 5-methylaminomethyl-2-thiouridine residue in the tRNA substrate to 5-methylaminomethyl-2-selenouridine. The selenium donor substrate for this reaction is shown to be selenophosphate which is formed from ATP and selenide by selenophosphate synthetase. Replacement of sulfur with selenium in tRNAs catalyzed by tRNA 2-selenouridine synthase occurs in the absence of ATP. The dependence of reaction velocity on selenophosphate concentration obeys Michaelis-Menten kinetics indicating an apparent Km value of 17.1 microM. Bulk thio-tRNA preparations from Escherichia coli and Salmonella typhimurium are equally effective as substrates for the selenium incorporation reaction. An intact 3' end of the tRNA molecule does not seem to be essential for selenium incorporation. Identity of the product of the reaction was confirmed by HPLC analysis of digests of [75Se]seleno-tRNAs labeled by incubation with the purified enzyme. A labeled compound in the nucleoside mixture was coeluted with authentic 5-methylaminomethyl-2-selenouridine.